Tourism promotion through vlog advertising and customer engagement behaviours of generation Z - Zaib Abbasi, A. (Routledge, 2022)
This study investigates the effectiveness of Vlogs as an advertising tool to promote the tourism sector in Pakistan using Ducoffeâs Advertising Value Model and stimulus-organism-response (S-O-R) framework, and its subsequent effect on customer engagement behaviours (CEBs). Data were collected from generation Z through both the online and offline medium, 230 students were approached; 206 questionnaires were usable for analysis. Partial least squaresâstructural equation modelling (PLS-SEM) was used for model assessment. The results indicated that all the relationships are supported: informativeness, entertainment, credibility and irritation significantly influence advertising value; adverting value influences attitude towards Vlog; and finally, attitude towards Vlog significantly influences electronic word-of-mouth (eWOM), positive word-of-mouth (PWOM), customer referral, and destination visit intention. This study is the first in this domain that measures the importance of Vlog advertising value in shaping the attitude of generation Z toward Vlog destination advertising, especially in the context of Pakistan, a developing economy. The theoretical and practical implications of the findings, limitations of the study and suggestions for future research directions are also discussed. Â© 2022 Informa UK Limited, trading as Taylor & Francis Group.